P45 Age-11 IQ, education level and age-60 sleep quality: a quantitative study using the newcastle thousand families study birth cohort. (26th August 2022) - Grebby, Jess; Slack, Emma; Pearce, Mark
Abstract : Background: Poor sleep quality has been linked to a number of adverse health outcomes. It is therefore important to understand factors contributing to sleep quality. Previous research has suggested that increased IQ and education duration have a protective effect on sleep quality in old age. A proposed mechanism is that higher intelligence quotient (IQ) and education levels contribute to increased cortical thickness, which in turn contributes to a higher overall sleep quality. That said, there have been very few studies examining this link directly. This study attempts to add to the body of research on the topic with the hypothesis that age-11 IQ and highest achieved education level are significantly associated with subjective sleep quality at age 60. Methods: Poor sleep quality has been linked to a number of adverse health outcomes. It is therefore important to understand factors contributing to sleep quality. Previous research has suggested that increased IQ and education duration have a protective effect on sleep quality in old age. A proposed mechanism is that higher intelligence quotient (IQ) and education levels contribute to increased cortical thickness, which in turn contributes to a higher overall sleep quality. That said, there have been very few studies examining this link directly. This study attempts to add to the body of research on the topic with the hypothesis that age-11 IQ and highest achieved education level are significantly associated with subjective sleep quality at age 60. Results: After excluding participants with incomplete data sets and those who had been diagnosed with sleep apnoea, 251 of 1142 participants were included in the path analysis model. Education level was significantly associated with global PSQI (R=-0.653; 95% CI –1.161, -0.145; p=0.012) but age-11 IQ was not. The model was stratified by sex, giving an improved fit in the women's model (n=141; RMSEA=0.031; CFI=0.997) but a poorer fit in the men's (n=110; RMSEA=0.302; CFI=0.841). In women, education level but not age-11 IQ was once again found to be significantly associated with global PSQI (R=-0.872; 95% CI –1.628, -0.115; p=0.024), but in the men's model neither age-11 IQ nor education level were significant. Neither social class score was significant in any of the models. Conclusion: The results of this study show a relationship between education level, but not childhood IQ and sleep quality in later life, in women only. Limitations of this study include the lack of brain imaging data, meaning the mechanism of the relationship cannot be ascertained.